DNM2 levels normalization improves muscle phenotypes of a novel mouse model for moderate centronuclear myopathy - Juliana de Carvalho Neves; Foteini Moschovaki-Filippidou; Johann Böhm; Jocelyn Laporte (Elsevier, 2023)
Dynamin 2 (DNM2) is a ubiquitously expressed GTPase regulating membrane trafficking and cytoskeleton dynamics. Heterozygous dominant mutations in DNM2 cause centronuclear myopathy (CNM), associated with muscle weakness and atrophy and histopathological hallmarks as fiber hypotrophy and organelles mis-position. Different severities range from the severe neonatal onset form to the moderate form with childhood onset and to the mild adult onset form. No therapy is approved for CNM. Here we aimed to validate and rescue a mouse model for the moderate form of DNM2-CNM harboring the common DNM2 R369W missense mutation. Dnm2R369W/+ mice presented with increased DNM2 protein level in muscle and moderate CNM-like phenotypes with force deficit, muscle and fiber hypotrophy, impaired mTOR signaling, and progressive mitochondria and nuclei mis-position with age. Molecular analyses revealed a fiber type switch toward oxidative metabolism correlating with decreased force and alteration of mitophagy markers paralleling mitochondria structural defects. Normalization of DNM2 levels through intramuscular injection of AAV-shDnm2 targeting Dnm2 mRNA significantly improved histopathology and muscle and myofiber hypotrophy. These results showed that the Dnm2R369W/+ mouse is a faithful model for the moderate form of DNM2-CNM and revealed that DNM2 normalization after a short 4-week treatment is sufficient to improve the CNM phenotypes.